Aspek Aspek-Aspek Sosial Pada Cerpen Ulian Pipis Panes Karya Pandé Putu Alit Antara - Wahyu Sanjaya, I Wayan; Sutika, I Nyoman Duana; Suardiana, I Wayan (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2026)
This study aims to identify and describe the social aspects contained in the short story Ulian Pis Panes. The theory used for the analysis is the theory of literary sociology according to Ratna. The methods and techniques used are the method and technique of data collection carried out by reading the short story repeatedly, translating it from Balinese to Indonesian, and recording important information. The data analysis method used in this study is descriptive qualitative. The data analysis results stage uses an informal method supported by deductive techniques. The results of the study show that the short story Ulian Pis Panes reflects the social reality of society through the depiction of various aspects of life. The four main social aspects found include the aspect of kinship, which is seen through close relationships between family members; the economic aspect, which reflects the gap and struggle of life in society; the aspect of love, which is shown through attention and sacrifice between characters; and the aspect of morality, which reflects ethical values, responsibility, and mutual respect in social life. These four aspects show that literary works do not only function as entertainment, but also as a reflection of social and cultural values ​​that live in society. This short story indirectly invites readers to better understand and reflect on the social conditions around them.